The Relationship between Immunological Markers, Disease Free Survival and Overall Survival in Acute Myeloid Leukemia in North-West of Iran - Zohreh Sanaat; Yashar Amizadeh; Akbar Movasagpour Akbari; Roya Dolatkhah (International Journal of Hematology-Oncology and Stem Cell Research, 2010)
"nIntroduction: Acute myeloid leukemia (AML) is a clonal disease characterized by heterogeneous involvement of hematopoietic bone marrow cell populations. In AML patients, a variety of clinical and biologic parameters, including surface markers, have been examined for potential value in predicting treatment response and survival. By checking the myeloid, lymphoid and nonspecific markers on the blasts, we tested the hypothesis which the disease free survival and overall survival in AML could correlate with the expression of them. "nMethods: The immunophenotype was performed by multiparameter flow cytometry (FACS Caliber flow cytometry, Becton Dickinson). The prognostic significance of 16 antigens is taken separately in 207 adult AML patients. We applied statistical software of SPSS-13. In this analysis, we compared DFS and OS with each of the surface markers existence. "nResults: We could just find significant correlation in 4 of these markers. Those patients possessed CD3 blasts, had better overall survival (P=0.027). In contrast in CD33 patients, this parameter was worse (P=0.002). Disease free survival in CD15 patients was higher (P=0.036) but in CD34 cases, it was significantly lower (P=0.001). "nConclusions: This study suggests that dependent role of surface markers in the prognosis and response to treatment in AML is a fact which should be paid much more attention and applied it in the management of these patients.